In vitro and in vivo Efficacy of a Synergistic Combination of Itraconazole and Verapamil Against Aspergillus fumigatus - Zeng, Qiuqiong; Zhang, Zheng; Chen, Peiying; Long, Nanbiao; Lu, Ling; Sang, Hong (Frontiers in Microbiology, 2019)
The incidence of aspergillosis continues to rise sharply, while the progress made in enlarging the antifungal drug arsenal remains extremely slow, indicating an urgent need for new strategies. Previous studies have shown that the calcium signaling pathway, which are evolutionarily conserved in mammals and fungi, is involved in regulating the tolerance of azoles in fungi. In this study, we performed a preliminary screening among various combinations of different clinical calcium channel blockers and different anti-Aspergillus drugs. We found that the combination of itraconazole and verapamil showed the best synergistic effect against Aspergillus fumigatus. Thereafter, using the checkboard assays we observed synergistic effects of the combination treatment against most of the A. fumigatus strains tested, including itraconazole-sensitive and itraconazole-resistant strains, with a fractional inhibitory concentration index (FICI)<0.5. After verapamil pretreatment, cytosolic calcium transients following itraconazole stimulation determined by an aequorin-mediated method were strongly decreased. Moreover, verapamil influenced the efflux of rhodamine 6G, an azole mimic substance. An ergosterol assay revealed that verapamil alone has no effect on ergosterol biosynthesis, but the combination of itraconazole and verapamil treatment decreased the ergosterol level. Further murine assays were performed using a luciferase-probed bioluminescence imaging method. Drug combination therapy reduced lung burden and improved survival rate. In conclusion, verapamil is a promising candidate to enhance the antifungal activity of itraconazole against A. fumigatus. In addition, our study suggests the effectiveness of an emerging approach based on bioluminescence imaging in monitoring the efficacy of drug combination therapy for invasive aspergillosis.